Assessing the invasive potential of some species differing in habit and biogeographic origin under changing climate through ecological niche modelling - Ray D (National Seminar on Recent Trends in Biodiversity Conservation and Bioresource Utilization, 8-9 September 2017, Department of Botany, Womens College, Agarthala, India. Abstracts IL 5.)
Invasive potential of three weed species and one planted tree species differing in habit and bio-geographic origin were assessed through ecological niche modelling in the context of 2000 and 2050 climate in North-east India. Through this study, a basic question was attempted to be answered whether species with similar bio-geographic origin found in the inwaded range have any unique niche characteristics supporting the invasion process. This was observed that Ageratum conyzoides and Hevea brasiliensis with South American origin exhibited higher potential to invade/distribute in NE region of India by 2050. On the other hand, though Urena lobata and Imperata cylindrical are of South Asian origin, their potential to invade further in NE India is limited in 2050 compared to its past distribution in 2000. Climatic variable related to precipitation seasonality, temperature seasonality, temperature seasonality, mean temperature of warmest quarter and mean temperature of coldest quarter are some of the important factors that are responsible for better invasion of non-native species.
Keywords: Bioclimate; Invasion; Maxent; Northeast India; Species distribution modelling